(untitled) (Proceedings of International Educators Conference, 2023)
The article deals with impact on Charles Dickens’ works such as: “Bleak House”, “Little Dorrit”, “Nicholas Nickleby”, “Oliver Twist” to Evelyn Waugh’s A Handful of Dust.